Effect of multi-walled carbon nanotubes on phytotoxicity of sediments contaminated by phenanthrene and cadmium. (April 2017) - Song, Biao; Zeng, Guangming; Gong, Jilai; Zhang, Peng; Deng, Jiaqin; Deng, Canhui; Yan, Jin; Xu, Piao; Lai, Cui; Zhang, Chen; Cheng, Min
Abstract: To implement effective control and abatement programs for contaminants accumulating in sediments, strategies are needed for evaluating the quality of amended sediments. In this study, phytotoxicity of the sediments contaminated by cadmium and phenanthrene was evaluated after in situ remediation with multi-walled carbon nanotubes (MWCNTs) as adsorbents. Adsorption experiments and measurement of aqueous concentrations of the contaminants in overlying water were used to investigate the remediation effectiveness from physical and chemical aspects. The results indicated that MWCNTs showed a much better adsorption performance towards phenanthrene and Cd(II) compared with the sediments. The in situ remediation with MWCNTs could distinctly decrease the aqueous concentrations of phenanthrene and Cd(II) released from the sediments, reducing environmental risk towards overlying water. Influences of MWCNTs dose, MWCNTs diameter, and contact time on phtotoxicity of the contaminated sediments were studied. No significant inhibition of the amended sediments on germination of the test species was observed in the experiments, while the root growth was more sensitive than biomass production to the changes of contaminant concentrations. The analysis of Pearson correlation coefficients between evaluation indicators and associated remediation parameters suggested that phytotoxicity of sediments might inaccurately indicate the changes of pollutant content, but it was significant in reflecting the ecotoxicity of sediments after remediation. Highlights: Use of MWCNTs for in situ remediation of contaminated sediments was explored. Phytotoxicity of contaminated sediments before and after remediation was evaluated. Root growth was more sensitive to the changes of pollutant concentration. Phytotoxicity might inaccurately indicate the changes of pollutant content.